ANALISIS KESALAHAN PESERTA DIDIK KELAS VIII SMPN 10 PADANG DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIS BERDASARKAN TAHAPAN NEWMAN - Faul Zannah (Jurnal Edukasi dan Penelitian Matematika, 2021)
This paper will discuss the analysis of students’ errors in solving mathematical problem solving abilities question. Base on field data, clas VIII SMPN 10 Padang students still make a mistakes in solving mathematical problem solving problems. This is due to the various errprs of students and the absence of a detailed analysis of student errors. The porpose of this study is todescribe the type of errors made by students in solving mathematical problem solving problems along whit the factors that cause errors based on Newman’s stages.The approach of this research is a qualitative approach whit the descriptive type of research. Data obtained from the results of tests and interviews. Data were analyzed based on qualitative analysis tecniques, namely data reduction, data presentation and drawing conclusions. The results showed that there were studentswho made reading errors, comprehention errors, transformation errors, processing skills errors and encoding errors. The factors that cause students to make mistakes are internal and external factors. Keywords—Mathematical Problem Solving Ability, Newman’s Error Analysis